PERLINDUNGAN HUKUM PERSAMAAN KESELURUHAN MEREK TERKENAL STARBUCKS: Legal Protection Of The Overall Similarity Of The Famous Starbuck Trademark - Andri Suwandi; Dian Purnamasari (AMICUS CURIAE, 2025)
A brand is a sign that can be displayed graphically with the aim of distinguishing goods and/or services produced by a person or legal entity in the activity of trading goods and/or services. Starbucks Corporation is a company in the United States that has the rights to the Starbucks brand which was registered in the United States in 1976. However, there is a brand registration in Indonesia that has overall similarities with the Starbucks brand registered by PT Sumatra Tobacco Trading Company in 1992. This article discusses the issue of legal protection for the well-known Starbucks brand owned by Starbucks Corporation when it is registered in Indonesia when there is a brand that has overall similarities that has previously been registered in Indonesia. The type of research used is normative legal research with secondary data. The nature of the research is descriptive. Drawing conclusions using deductive reasoning. The conclusion of this article is that protection of the famous Starbucks brand owned by Starbucks Corporation is carried out by canceling the registration of the Starbucks brand owned by PT Sumatra Tobacco Trading Company which was previously registered in Indonesia on the grounds that it imitates the famous Starbucks brand owned by Starbucks Corporation.